PERANCANGAN SISTEM INFORMASI ABSENSI PEGAWAI BERBASIS WEB PADA KANTOR DESA SUKARENDAH KEC.WARUNGGUNUNG - Arief, Rahadian; Sapaatullah, Asep; Damayanti, Dwi Rosa (LPPM Universitas Bina Bangsa, 2023)
Attendance is a data retrieval activity to determine the number of attendance at a job, and the results of this study indicate that the application of web attendance at Sukalow Village Office employees tends to increase discipline towards employee attendance, with the support of detailed recorded data about the accuracy of employees entering and leaving the office..The purpose of this research is to analyze the registration information system. Helping villages to manage attendance to make it easier to do their attendance. Designing a web-based attendance information system.In designing this research the method used is a structured approach, the development method uses PIECES, the tool used to design the system is DFD, while to design and implement this financial information system using the PHP programming language, MySQL database and for the text editor using the Sublime text application. .The results of the research on employee attendance information systems when doing attendance are no longer manual but web-based.With the creation of a web- based attendance information system, it can make it easier for employees to do attendance and make it easier for officers to make attendance reports